2002
DOI: 10.1088/0953-8984/14/34/306
|View full text |Cite
|
Sign up to set email alerts
|

A study of the non-uniform effect on the shape anisotropy in patterned NiFe films of ferromagnetic resonance

Abstract: A systematic ferromagnetic resonance (FMR) study shows that an in-plane magnetic anisotropy in the patterned submicron rectangular permalloy elements is mainly determined by the element geometry. As the aspect ratio increases, the in-plane shape anisotropy increases, but the contribution from the non-uniform demagnetizing effect decreases. An expression is proposed to represent the in-plane shape anisotropy due to the non-uniform demagnetizing effect. When the magnetic field is applied near the film normal dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Chérif et al observed a difference between spin wave frequencies within the Brillouin light scattering ͑BLS͒ spectra measured with the bias magnetic field applied parallel to the edge and to the diagonal of rectangular elements. 8,9 The effect of the shape and configurational anisotropies upon the ferromagnetic resonance ͑FMR͒ mode was studied by Zhai et al 10 and more recently by Pardavi-Horvath et al 11 The spatial character of the anisotropic magnetization dynamics in micron sized square magnetic elements was directly studied by time resolved scanning Kerr microscopy ͑TRSKM͒ by Barman et al [12][13][14][15] In addition to the fourfold variation of the frequency of the uniform precessional mode, they found that the spatial character of magnetostatic modes of finite wave number depends sensitively upon the direction of the bias magnetic field, and the dephasing of the modes leads to an anisotropic apparent damping of the precessional signal.…”
Section: Introductionmentioning
confidence: 99%
“…Chérif et al observed a difference between spin wave frequencies within the Brillouin light scattering ͑BLS͒ spectra measured with the bias magnetic field applied parallel to the edge and to the diagonal of rectangular elements. 8,9 The effect of the shape and configurational anisotropies upon the ferromagnetic resonance ͑FMR͒ mode was studied by Zhai et al 10 and more recently by Pardavi-Horvath et al 11 The spatial character of the anisotropic magnetization dynamics in micron sized square magnetic elements was directly studied by time resolved scanning Kerr microscopy ͑TRSKM͒ by Barman et al [12][13][14][15] In addition to the fourfold variation of the frequency of the uniform precessional mode, they found that the spatial character of magnetostatic modes of finite wave number depends sensitively upon the direction of the bias magnetic field, and the dephasing of the modes leads to an anisotropic apparent damping of the precessional signal.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of nanoscale spatial resolution has been circumvented by measuring the frequency [16][17][18][19][20][21] or time 22,23 domain response from sufficiently large arrays of nanomagnets and comparing the measured signals with analytical theories [18][19][20] and/or micromagnetic simulations. 16,17,[21][22][23][24][25][26][27][28][29] In particular, this approach has led to the discovery of a crossover from a center to edge localized mode as the magnetic element size is reduced to less than 220 nm. 22,23 In this paper, numerical simulations performed with the object oriented micromagnetic framework 30 ͑OOMMF͒ have been used to study various factors affecting the high frequency response of the nanoscale magnetic elements, and the degree to which such simulations can reproduce the data reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…͓DOI: 10.1063/1.1849057͔ Patterned thin film magnetic materials are one of the main subjects of investigation within modern magnetism. The dynamical properties of these materials have been studied experimentally by Brillouin light scattering, 1 time resolved scanning Kerr microscopy 2 ͑TRSKM͒, ferromagnetic resonance, 3,4 and pulsed inductive microwave magnetometry. 5 However, current experimental methods do not yet provide sufficient spatial resolution for the dynamical properties of a single nanoscale element to be studied directly.…”
mentioning
confidence: 99%
“…Consequently the magnetic properties of the element must be deduced from measurements made on the entire array. 1, 3,4 In this article, measurements of the precessional dynamics in Ni 88 Fe 12 ͑27 Å͒ /Co 80 Fe 20 ͑10 Å͒ single microelement and nanoelement arrays are presented, using the TR-SKM as a submicron probe of the magnetization dynamics at the center of a sample.…”
mentioning
confidence: 99%